Convergence technologies for 3G networks : IP, UMTS, EGPRS and ATM - Bannister, Jeffrey (Wiley, 2004)
The merging of voice and data on a single network opens powerful new possibilities in communications. Only a fundamental understanding of both technologies will ensure you are equipped to maximise their full potential.℗¡Convergence Technologies for 3G Networks describes the evolution from cellular to a converged network that integrates traditional telecommunications and the technology of the Internet.℗¡